Analysing and measuring the impact of the structural imbalance of the Saudi economy on the balance of the general budget for the period 1990-2021 - Mohammed Salih* , Zozan; Abdulrahman Aldosakee , Rijwan J.; Ismael Haso, Sarkar (Journal of Economics and Administrative Sciences, 2024)
The research aims to show the impact of structural imbalances in the main sectors in the Kingdom of Saudi Arabia by testing the relationship in the short and long term between the variables of the structure of the main sectors of industry, agriculture, and mining, in addition to the price of oil as independent variables, and between the public budget expressed by 1990-2021. The results have resulted in a long-term relationship between the main sectors and the oil price and between the deficit and the surplus of the general budget with a negative correction factor of (-0.77) in order to return to the equilibrium situation in the short term and the long term, and the research reached a set of conclusions that the changing price of oil was not significant; in other words, it did not have a clear impact on the general budget. As for the agriculture sector, it has had a significant negative impact on the public budget in Saudi Arabia in the long term. The influence of both the mining sector and the industrial sector had a positive impact on the balance sheet. The research suggests that the government of the Kingdom should continue to implement the structural reforms adopted during the Kingdom’s vision 2030 in diversifying the economic and production base and reducing dependence on oil revenues, which will positively reflect on its financial sustainability and raise the rates of non-oil gross domestic product. Paper type: Research Paper